The Effectiveness of Giving Jasmine and Kasturi Aromatherapy on Reducing Anxiety in Postpartum Mothers - Fitria, Lia; Arifin, Arifah (Universitas Pahlawan Tuanku Tambusai, 2024)
During the postpartum period, there will be changes in adaptation, both physiological and psychological. Postpartum mothers may experience psychological disorders during the postpartum period. One of the psychological disorders during the puerperium is anxiety. Aromatherapy is a relaxation technique using essential oils made from plants which are useful for reducing stress, anxiety and calming the mind. The purpose of this study was to analyze the effectiveness of giving jasmine and kasturi aromatherapy to reducing anxiety in postpartum mothers. The research method used is quasi experiment, Non Equivalent Group Design using pretest – posttest. Data collection was carried out by observing 2 groups of postpartum women, namely 15 respondents were given jasmine aromatherapy and 15 respondents were given kasturi aromatherapy. The number of respondents was 30, the measurement used an anxiety questionnaire sheet (Zung Self-Rating Anxiety Scale). Data analysis used the Independent Sample T-Test with a significance level of ? = 0.05. The results of this study showed that the difference in decreasing anxiety in jasmine aromatherapy was 4.96 ± 0.15, while in the kasturi aromatherapy group the average decrease in anxiety was 4.01 ± 0.067 with a P value <0.002 which indicated a significant relationship. The conclusion of this study is that giving jasmine and kasturi aromatherapy can reduce anxiety in postpartum mothers, but the jasmine aromatherapy group has a higher anxiety reduction score than the kasturi aromatherapy group. Keywords: Anxiety, Postpartum Mother, Jasmine Aromatherapy, Kasturi Aromatherapy